2003
DOI: 10.1203/01.pdr.0000090927.53818.de
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E Genotype Predicts 24-Month Bayley Scales Infant Development Score

Abstract: Apolipoprotein E (APOE) regulates cholesterol and fatty acid metabolism, and may mediate synaptogenesis during neurodevelopment. To our knowledge, the effects of APOE4 isoforms on infant development have not been studied. This study was nested within a cohort of mother-infant pairs living in and around Mexico City. A multiple linear regression model was constructed using the 24-mo Mental Development Index (MDI) of the Bayley Scale as the primary outcome and infant APOE genotype as the primary risk factor of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
117
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(133 citation statements)
references
References 38 publications
12
117
4
Order By: Relevance
“…These findings support the recent proposition of APOE e4 antagonistic pleitropy (Han and Bondi, 2008;Wright et al, 2003), whereby the e4 variant might have contrasting effects across the lifespan. Our results suggest that this labile cognitive profile of e4 carriers may be related to and influenced by the integrity of the cholinergic system.…”
Section: Discussionsupporting
confidence: 89%
“…These findings support the recent proposition of APOE e4 antagonistic pleitropy (Han and Bondi, 2008;Wright et al, 2003), whereby the e4 variant might have contrasting effects across the lifespan. Our results suggest that this labile cognitive profile of e4 carriers may be related to and influenced by the integrity of the cholinergic system.…”
Section: Discussionsupporting
confidence: 89%
“…Indeed, the only difference between groups reflected better performance on the VMI among children with the allele. Other studies have reported better neuropsychological test performance among individuals with the e4 allele following TBI (Blackman et al, 2005;Han et al, 2007), and some researchers posit that the allele may serve a protective function during neurodevelopment (Oria et al, 2005;Wright et al, 2003). However, our findings of a positive effect are limited to only one cognitive outcome measure, and hence may not be robust.…”
Section: Discussioncontrasting
confidence: 73%
“…Hence the associations of APOE4 with protection against diarrhea and its subsequent cognitive decline seen in our studies and in those Mexican infants [70] bolster the need for experimental documentation of these relationships, their causality, and the ability of specific micronutrients to ameliorate the lasting effects of malnutrition in individuals lacking APOE4.…”
Section: Children Carrying Apoe4 Show a Developmental Benefit Againstsupporting
confidence: 51%